Relationship among EEG patterns, spatial memory and cell loss in neural degeneration induced by kainic acid or dexamethasone and in aging rats - Acharaporn Issuriya (Prince of Songkla University, 2015)
Thesis (M.Sc. (Physiology))--Prince of Songkla University, 2014